Melatonin protects endothelial progenitor cells against AGE-induced apoptosis via autophagy flux stimulation and promotes wound healing in diabetic mice - Jin, Haiming; Zhang, Zengjie; Wang, Chengui; Tang, Qian; Wang, Jianle; Bai, Xueqin; Wang, Qingqing; Nisar, Majid; Tian, Naifeng; Wang, Quan; Mao, Cong; Zhang, Xiaolei; et al. (Experimental & molecular medicine, 2018)
Wound healing is delayed in diabetic patients. Increased apoptosis and endothelial progenitor cell (EPC) dysfunction are implicated in delayed diabetic wound healing. Melatonin, a major secretory product of the pineal gland, promotes diabetic wound healing; however, its mechanism of action remains unclear. Here, EPCs were isolated from the bone marrow of mice. Treatment of EPCs with melatonin alleviated advanced glycation end product (AGE)-induced apoptosis and cellular dysfunction. We further examined autophagy flux after melatonin treatment and found increased light chain 3 (LC3) and p62 protein levels in AGE-treated EPCs. However, lysosome-associated membrane protein 2 expression was decreased, indicating that autophagy flux was impaired in EPCs treated with AGEs. We then evaluated autophagy flux after melatonin treatment and found that melatonin increased the LC3 levels, but attenuated the accumulation of p62, suggesting a stimulatory effect of melatonin on autophagy flux. Blockage of autophagy flux by chloroquine partially abolished the protective effects of melatonin, indicating that autophagy flux is involved in the protective effects of melatonin. Furthermore, we found that the AMPK/mTOR signaling pathway is involved in autophagy flux stimulation by melatonin. An in vivo study also illustrated that melatonin treatment ameliorated impaired wound healing in a streptozotocin-induced diabetic wound healing model. Thus, our study shows that melatonin protects EPCs against apoptosis and dysfunction via autophagy flux stimulation and ameliorates impaired wound healing in vivo, providing insight into its mechanism of action in diabetic wound healing. Diabetes: Healing old wounds Melatonin, a sleep-regulating hormone, may speed wound healing in patients with diabetes by protecting blood-borne wound-healing cells known as endothelial progenitor cells (EPCs). In diabetes, EPCs become damaged, lose their capacity to migrate to wounds and form new tissue, and die prematurely. Delayed healing can lead to ulcers, infection, and sometimes amputation. Melatonin has recently been reported to promote wound healing, but the mechanism remains unclear. Xiangyang Wang and Xiaolei Zhang at Wenzhou Medical University, China, and coworkers hypothesized that melatonin might protect EPCs from diabetes-induced damage. They found that melatonin improved EPCs’ ability to eliminate damaged components, allowing them to repair themselves and restoring their wound-healing function. In further experiments, diabetic mice treated with melatonin healed faster than untreated mice. These results may help improve treatments for complications of diabetes.